Evaluation of the Effect of Workshops Oriented to Parents Whose Children Present First Psychotic Episodes [Evaluación del Efecto de Talleres Orientados a Padres Cuyos Hijos Presentan Primeros Episodios Psicóticos] - Loubat-Oyarce, M (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2012)
The effectiveness of a Psycho-Educational Workshop oriented to parents with children undergoing first psychotic episodes is evaluated. The Workshop is aimed at promoting strategies for confronting the pathology, reducing stress, anxiety, and depression in the parents, to produce an effect on the treatment of the youngsters. This research was done in the framework of the "Treatment of People from the First Episode of Schizophrenia" Program of Chilean Public health. It is an explicative study based on a pre-experimental design, with pre- and post- intervention measurements with a non-probabilistic and intentional sample of 55 parents distributed randomly in five workshops of 12 sessions each. The results show the use of planned active confrontation strategies, controlling emotion and using preferentially cognitive activity, also achieving decreased anxiety, stress, and depression indicators in the parents. It is concluded that it is important to incorporate the theme of confrontation strategies by the parents in the psychoeducational workshops, particularly in the initial stage of the disorder.